A cluster collaborative synchronisation dynamic model of the dissipative coupling supply chain network. (26th October 2020) - Yang, Bing; Zhao, Gang; Hu, Ming-hua; Liu, Chang-ping; Yang, Ying-bao
The supply chain network is regarded as a dynamic system consisting of member companies with dynamic behaviours. In this paper an attempt is made to describe the dynamic behaviours of each member company with an autonomous dynamic system to establish the cluster collaborative synchronisation dynamic model for dissipative coupling supply chain networks. Considering the materials flow, transaction amount and substitutability among the member companies of the supply chain network, a collaborative closeness matrix of the supply chain network was set. Based on the proposed model, the cluster collaborative synchronisation interval of the supply chain network was calculated and the simulation results were obtained. This model is not proved to be suitable for the general scale supply networks, but also suitable for the large-scale complex supply chain networks. Based on the proposed model and the cluster collaborative synchronisation interval, we can optimise strategy for the collaborative synchronisation operation among the member companies of the supply chain network.